Pengaruh Lingkungan Kerja Fisik Dan Non Fisik Terhadap Produktivitas Kerja Pegawai Dinas Pendidikan Provinsi Sulawesi Selatan - Nadha Auliya; Akhmad, Akhmad; Mellisyah, Mellisyah (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to 1) determine the effect to the physical work environmenton the work productivity of employees of the south sulawesi provincial education office. 2) to determine the effect of the non physical work environment on the work productivity of employees of the south Sulawesi provincial education office. The type of research conductedis quantitative with an associative approach, the population in this study were all employees at the south Sulawesi provincial education office totaling 114 people. The results of this study physical work environment has a positive and significant effect on employee work productivity. Therefore, efforts to improve the comfort of the work space through periodic evalutions are very important to increase focus, reduce fatigue, and increase the work efficiency of employees of the south Sulawesi provincial education office. Non physical work environment has positive and significant effect on employee work productivity. This is very important to achieve organizational success and increase the work efficiency of employees of the south Sulawesi provincial education office.